More Choices or More Trust? Investigating Product Variety, Online Reviews, and Trust in Café Purchase Decisions - Gita Mutiara Annisa Chaerani; Hana Alfira (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study analyzes the influence of product variety, online reviews, and trust on purchasing decisions at café in Jakarta. The population of this study consisted of café customers in Jakarta. The sample consisted of 180 respondents selected using purposive sampling. Data analysis was performed using multiple linear regression with SPSS. The results of this study indicate that product variety, online reviews, and trust simultaneously influence purchasing decisions. Trust partially influences purchasing decisions. Meanwhile, product variety and online reviews do not influence purchasing decisions. These results emphasize the importance of building and maintaining consumer trust as a key strategy in improving purchasing decisions.